Drug dependence (Psicologia USP, 2006)
This paper analyses three current theories about drug dependence: Heyman´s Behavioral Theory of dependence as choice, Robinson and Berridge´s incentive-Sensitization Theory, and Kalivas´ Neurobiological Theory of dependence as choice. All of them agree in defining dependence as a phenomenon resulting from learning processes in which drug and associated stimuli acquire powerful control over behavior. The three theories diverge as to the specific learning processes that could explain dependence. The Behavioral Theory emphasizes the operant component, sustaining that repeated ingestion of a drug reduces the reinforcing value of concurrent activities. Incentive-sensitization theory gives priority to the respondent component, advancing that dependence results from sensitization of the eliciting power of stimuli associated to the drug effect. The Neurobiological Theory integrates the former two by describing the changes that occur in the reinforcement circuit as dependence develops.